2019
DOI: 10.1002/dev.21836
|View full text |Cite
|
Sign up to set email alerts
|

Fathering across contexts: The moderating role of respiratory sinus arrhythmia in predicting toddler emotion regulation

Abstract: Caregivers play an integral role in promoting children's emotion regulation, while children's individual physiology affects how they respond to the caregiving environment. Relatively little is known about how fathering influences toddler emotion regulation, particularly within African American and low‐income communities, where risk related to the development of emotion regulation is higher. This study investigated relations among fathering, toddler parasympathetic regulation, and toddler emotion regulation in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 113 publications
1
12
0
1
Order By: Relevance
“…These findings illustrate meaningful differences in mother–child and father–child RSA synchrony in early childhood, adding to a growing body of literature showing that fathers and mothers interact differently with their children (John et al., 2013; Kochanska et al., 2015; Richardson et al., 2019). Synchrony with fathers may be more influenced by salient, observable behaviors such as positive affect than by more trait‐like characteristics or capacities in the child.…”
Section: Discussionsupporting
confidence: 66%
“…These findings illustrate meaningful differences in mother–child and father–child RSA synchrony in early childhood, adding to a growing body of literature showing that fathers and mothers interact differently with their children (John et al., 2013; Kochanska et al., 2015; Richardson et al., 2019). Synchrony with fathers may be more influenced by salient, observable behaviors such as positive affect than by more trait‐like characteristics or capacities in the child.…”
Section: Discussionsupporting
confidence: 66%
“…Alternatively, parents of children with lower average RSA may be even more attuned to their children due to their higher needs for external regulation. Second, recent findings suggest that average RSA constitutes a biological susceptibility to environmental influences, influencing how children react and respond to negative or positive qualities of the caregiving environment (Eisenberg et al., 2012; Richardson et al., 2019). For example, children with higher average RSA may be more sensitive to external influences such as parent physiology and behavior than children with lower average RSA (Eisenberg et al., 2012; Richardson et al., 2019).…”
Section: Average Rsa As a Moderator Of Rsa Synchronymentioning
confidence: 99%
“…Second, recent findings suggest that average RSA constitutes a biological susceptibility to environmental influences, influencing how children react and respond to negative or positive qualities of the caregiving environment (Eisenberg et al., 2012; Richardson et al., 2019). For example, children with higher average RSA may be more sensitive to external influences such as parent physiology and behavior than children with lower average RSA (Eisenberg et al., 2012; Richardson et al., 2019). Although continued work is needed to better understand its role in dyadic RSA, recent studies showed that child average RSA interacted with parental psychological distress and child externalizing symptoms to shape parent–preschooler RSA synchrony (Fuchs et al., 2021; Lunkenheimer et al., 2021), underscoring its relevance for RSA synchrony.…”
Section: Average Rsa As a Moderator Of Rsa Synchronymentioning
confidence: 99%
“…In contrast to the burgeoning research on infant biological characteristics that interact with maternal caregiving to influence child outcomes, only a few researchers have examined children's susceptibility to paternal engagement in caregiving. Among a sample of predominantly low‐income, Black children, those with moderate and higher resting RSA were more susceptible to the effects of paternal engagement on toddler emotion regulation, such that these children were likely to have better emotion regulation when their fathers were more engaged (Richardson et al., 2019). Boyce et al.…”
Section: Introductionmentioning
confidence: 99%